Materiales educativos y el aprendizaje en matemática en los niños de la Institución Educativa Inicial N°657, Punchana 2023 - Mozombite Murayari, Danni Maritza (2024)
The objective of the research was to determine the relationship between the use of educational materials and mathematics learning in boys and girls of the Initial Educational Institution No. 657 Punchana during the year 2023. A quantitative approach and a correlational design were adopted for the study, with a population made up of 159 boys and girls. To collect data, the observation technique was used, using an observation guide as an instrument, which was validated by three experts in the area. The results obtained showed a Spearman's Rho correlation coefficient of 0.735, evidencing a moderate-high positive correlation between the variables studied. Furthermore, the significance value (p = 0.05) indicated that the correlation is statistically significant. It was concluded that there is a relationship between the use of educational materials and mathematics learning in children.